Elephant grass genotypes for bioenergy production by direct biomass combustion - Morais, Rafael Fiusa de; Souza, Bruno Juscelino de; Leite, José Marcos; Soares, Luis Henrique de Barros; Alves, Bruno José Rodrigues; Boddey, Robert Michael; Urquiaga, Segundo (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate elephant grass (Pennisetum purpureum Schum.) genotypes for bioenergy production by direct biomass combustion. Five elephant grass genotypes grown in two different soil types, both of low fertility, were evaluated. The experiment was carried out at Embrapa Agrobiologia field station in Seropédica, RJ, Brazil. The design was in randomized complete blocks, with split plots and four replicates. The genotypes studied were Cameroon, Bag 02, Gramafante, Roxo and CNPGL F06-3. Evaluations were made for biomass production, total biomass nitrogen, biomass nitrogen from biological fixation, carbon/nitrogen and stem/leaf ratios, and contents of fiber, lignin, cellulose and ash. The dry matter yields ranged from 45 to 67 Mg ha-1. Genotype Roxo had the lowest yield and genotypes Bag 02 and Cameroon had the highest ones. The biomass nitrogen accumulation varied from 240 to 343 kg ha-1. The plant nitrogen from biological fixation was 51% in average. The carbon/nitrogen and stem/leaf ratios and the contents of fiber, lignin, cellulose and ash did not vary among the genotypes. The five genotypes are suitable for energy production through combustion.